Structure-activity relationships of natural and non-natural amino acid-based amide and 2-oxoamide inhibitors of human phospholipase A2 enzymes - Antonopoulou, G.; Barbayianni, E.; Magrioti, V.; Cotton, N.; Stephens, D.; Constantinou-Kokotou, V.; Dennis, E. A.; Kokotos, G. (Bioorganic and Medicinal Chemistry, 2008)
A variety of 2-oxoamides and related amides based on natural and non-natural amino acids were synthesized. Their activity on two human intracellular phospholipases (GIVA cPLA2 and GVIA iPLA2) and one human secretory phospholipase (GV sPLA2) was evaluated. We show that an amide based on (R)-γ-norleucine is a highly selective inhibitor of GV sPLA2.
Keywords: 2-Oxoamides; Amides; Amino acids; Inhibitors; Phospholipase A2